Educators’ Role in Mitigating Suicidal Propensities among Zimbabwe Rural Secondary Male Learners: An Exploration of Challenges and Interventions Mechanisms - Saruchera, Munyaradzi; Chidarikire, Munyaradzi (Research in Social Sciences and Technology, 2025)
This qualitative study explores the role of educators in addressing and mitigating suicidal propensities among male rural secondary school learners in Zimbabwe. Then, it focuses on educators’ challenges and intervention mechanisms to provide insights into practical strategies for supporting mental health in this vulnerable population. Grounded in a phenomenological approach, the study utilizes a case study design to explore the lived experiences of 14 participants, including educators, parents, and health professionals. Data collection through focus group discussions enables a nuanced understanding of the complexities surrounding suicide prevention in rural educational settings. Research findings indicate that educators frequently struggle to identify suicidal tendencies among male learners due to cultural stigma surrounding mental health and lack of training in psychological assessment. Communication gaps with parents and health professionals further complicate these challenges. Conversely, successful intervention mechanisms identified in the study include peer support programs and mental health awareness campaigns, which create supportive environments and empower learners to seek help and engage in open discussions about mental health. Based on these findings, the study recommends that educational authorities implement comprehensive training programs for educators to equip them with the necessary skills to identify and address suicidal propensities among learners. Such training should encompass mental health education, communication strategies, and cultural sensitivity. Furthermore, establishing partnerships between schools and local health services can enhance the support system for vulnerable learners. Collaborative initiatives should be developed to facilitate regular mental health screenings and provide accessible resources for learners and their families.